2017
DOI: 10.1080/21645515.2017.1398297
|View full text |Cite
|
Sign up to set email alerts
|

Is hepatitis B vaccination performed at infant and adolescent age able to provide long-term immunological memory? An observational study on healthcare students and workers in Florence, Italy

Abstract: Universal vaccination programmes against Hepatitis B Virus (HBV) have significantly reduced the burden of the disease; nevertheless, HBV infection remains a relevant issue for high-risk subjects, such as healthcare workers (HCWs), who may potentially be exposed to blood or body fluids. Our study evaluates the long-term duration of the immunological memory of HBV vaccination 11-23 years after primary immunization by examining the response to booster doses in HCWs and students of health disciplines at Careggi Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 14 publications
2
15
1
2
Order By: Relevance
“…This finding confirms the current knowledge concerning the long-term persistence of seroprotection levels in appropriately vaccinated subjects, as described in the literature [24, 25]. …”
Section: Discussionsupporting
confidence: 92%
“…This finding confirms the current knowledge concerning the long-term persistence of seroprotection levels in appropriately vaccinated subjects, as described in the literature [24, 25]. …”
Section: Discussionsupporting
confidence: 92%
“…20 The present study integrates data that we have recently presented on long-term immunological memory after the vaccination against HBV. 16 In this previous publication, we presented 330 HCWs and students of the health sector with non-protective antibody titers (anti-HBs <10 mlU/mL) after the primary vaccination course, who received a challenge dose of vaccine in order to elicit an anamnestic response. The measurement of the antibody levels 1 month after this further dose showed that 11.2% (n.37) still had anti-HBs titer <10 mIU/mL and they were regarded as primary vaccination failures; a significantly higher proportion of them were vaccinated during adolescence (p < .001).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous publication, we reported only four people who accepted the fifth vaccine dose. 16 This extension of the study allows us to present a larger number of subjects who continued the proposed second vaccination course, thus adding relevant information on the foreseeable gain of each additional dose to overcome the non-responder status: in particular, 42 subjects who were still seronegative after the challenge dose (fourth dose after the basic vaccination course), accepted the fifth dose. The anti-HBs titer check at 1 month showed that 76.2% of them responded, implying that insistence in administering further doses after the fourth is of crucial importance to overcome the non-responder status in high-risk subjects like HCWs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diferentes estudios de seroprevalencia muestran una variabilidad en los resultados de títulos de anticuerpos anti-HBs protectores, oscilando de los 69,8% (20) y 70,7% (21) , registrados en trabajadores sanitarios con vinculación laboral en centros del norte de Italia, a prevalencias del 92,2% en estudios realizados en Turkia (22) . En caso de España, los niveles de anticuerpos protectores publicados entre los profesionales sanitarios son bajos, alcanzándose registros del 64,4% (12) , no obstante, debemos destacar, una progresiva reducción del interés científico en estudios de control serológico en trabajadores sanitarios tras las introducción de la vacunación sistemática.…”
Section: Introductionunclassified